University experience of a tutorial action programme during the COVID-19 lockdown in teacher training at a Valencian University (Spain) - Martínez-Bello, Vladimir E.; Díaz-Barahona, José; Bernabé-Villodre, María del Mar (Actualidades Investigativas en Educación, 2021)
Coronavirus disease 2019 (COVID-19) is perceived as the worst modern-times pandemic. This entirely new health situation entailed a new challenge to the education system. To our knowledge, the impact of alternative teaching methods derived from the social distancing imposed by COVID-19 on university student perception in teacher education has not been investigated. The aim of this study was to analyse an educative experience developed in a Faculty of Teaching from March 2020 to July 2020 in order to overcome the challenge imposed by COVID-19. A qualitative approach was used for data collection and analysis using four information sources: (a) The final written documents developed by the working groups (b) The online oral presentation of their work (c) The semi-structured interviews conducted through videoconferencing during the lockdown and, (d) The focus groups meetings. We have identified 8 major categories. Our results show that: (a) students find videoconferences are a tool that offsets the issues of social distancing; (b) intrinsic motivation is essential to overcome the perceived barriers; (c) the move to a virtual environment allowed students to deepen their methodological skills; (d) students now see themselves more competent regarding academic information research; e) the constant interaction among group members and the teacher is a key element to achieve a positive experience during social isolation; (f) new logistic and operational dynamics for cooperative working were constructed as a result of using videoconferences. We highlighted the barriers and facilitators perceived by students during the implementation of a tutorial action during the COVID-19 pandemic.